Transformasi Pembelajaran Informatika Berbasis Digital: Studi Eksperimen Proyek TikTok terhadap Capaian Belajar Siswa Kelas XI - Hudiya Mubarokah; Vera Irma Delianti (Lembaga Yasin AlSys, 2025)
The limited number of studies on the transformation of digital-based informatics learning through social media platforms serves as the background for this research, despite the phenomenon’s substantial potential to enhance student learning outcomes in the digital era. This study aims to analyze the impact of implementing a TikTok project on the learning outcomes of Grade XI students in informatics and to assess the effectiveness of digital-based learning transformation. A quantitative approach was employed using a pre-experimental One-Group Pretest-Posttest Design. The sample consisted of 30 Grade XI F8 students from SMAN 1 Gunung Talang, selected through purposive sampling. The research instrument comprised a 34-item multiple-choice informatics achievement test that had been previously validated. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and N-Gain calculation. The results revealed a significant improvement in learning outcomes, with the average score increasing from 47.37 (pretest) to 90.30 (posttest), representing a 90.5% increase. The mean N-Gain score of 0.82 falls into the high category, with 90% of students demonstrating high improvement and 10% moderate improvement. The paired sample t-test yielded a p-value of 0.000 (< 0.05), and Cohen’s d effect size was calculated at 2.904, indicating a very large effect. The study concludes that the implementation of the TikTok project is highly effective in enhancing student learning outcomes and shows strong potential as an innovative model for digital-based informatics learning transformation. The implications include a theoretical contribution to the literature on digital learning and the opening of avenues for further research on the use of other digital platforms and the development of hybrid learning models that integrate technology and pedagogy.